The Effect of Work Environment Condition and Job Satisfaction on Employees Engagement and Organizational Citizenship Behavior on Non-Medical Workers - Dina Silvia Sutarya; Dini Suryani; Muhammad Fauzul Akbar; Sekar Wulan Prasetyaningtyas (Green Publisher Indonesia, 2023)
This study uses to describe the Work Environment Condition, Job Satisfaction and Employee Engagement on OCB in hospitals in Banjarbaru city. The purpose of this paper is to find out how big the impact of Work Environment Condition and job satisfaction on Employees Engagement and Organizational Citizenship Behavior in the health industry, especially in Banjarbaru City. The type of data that researchers collect for this study is use quantitative research and researcher examines the relationship of each variable to be hypothesized, and finds out whether the variable is influenced by other variables. This study used data collection techniques with the likert scale method. Population in this study were non-medical employees at the Banjarbaru City Hospitals. This study used PLS with boothstrap resampling methodology to test hypotheses. The test result of this analysis shows that all variables have an impact on another one. Then it can be concluded, organizations that are able to build OCB attitudes towards their employees tend to be better in terms of performance because non-medical employees work wholeheartedly in providing services so that hospitals need to reward non-medical employees with good performance so that they feel satisfied in their work.